Early epidemiological investigations: World Health Organization UNITY protocols provide a standardized and timely international investigation framework during the COVID‐19 pandemic. Issue 1 (5th October 2021) - Bergeri, Isabel; Lewis, Hannah C.; Subissi, Lorenzo; Nardone, Anthony; Valenciano, Marta; Cheng, Brianna; Glonti, Ketevan; Williams, Bridget; Abejirinde, Ibukun‐Oluwa Omolade; Simniceanu, Alice; Cassini, Alessandro; Grant, Rebecca; et al.
Abstract : Background: The declaration of Coronavirus disease 2019 (COVID‐19) as a Public Health Emergency of International Concern (PHEIC) on 30 January 2020 required rapid implementation of early investigations to inform appropriate national and global public health actions. Methods: The suite of existing pandemic preparedness generic epidemiological early investigation protocols was rapidly adapted for COVID‐19, branded the 'UNITY studies' and promoted globally for the implementation of standardized and quality studies. Ten protocols were developed investigating household (HH) transmission, the first few cases (FFX), population seroprevalence (SEROPREV), health facilities transmission (n = 2), vaccine effectiveness (n = 2), pregnancy outcomes and transmission, school transmission, and surface contamination. Implementation was supported by WHO and its partners globally, with emphasis to support building surveillance and research capacities in low‐ and middle‐income countries (LMIC). Results: WHO generic protocols were rapidly developed and published on the WHO website, 5/10 protocols within the first 3 months of the response. As of 30 June 2021, 172 investigations were implemented by 97 countries, of which 62 (64%) were LMIC. The majority of countries implemented population seroprevalence (71 countries) and first few cases/household transmission (37 countries) studies. Conclusion: The widespread adoption of UNITY protocols across all WHO regions indicates that they addressed subnational and national needs to support local public health decision‐making to prevent and control the pandemic.